Pengaruh Integrated Marketing Communication (IMC) Terhadap Brand Equity (Studi Pada PT. Bank Mandiri Persero Tbk. Cabang Jakarta Gedung Jaya ) - Dhila Nofia Azhari; N Rachma; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe aims of this study is to examine the effect of Integrated Marketing Communication (IMC) on Branding Equity of PT. Bank Mandiri Persero Tbk. Branch Jakarta Gedung Jaya.The population of this study is the consumer of PT. Bank Mandiri Branch Jakarta Gedung Jaya. The researcher select 90 samples of customer using purposive sampling method. The data in this study is gained from multiple linear regression, classical assumption and hypothesis test.The results of this study indicate that advertising, personal selling, public relations, and event have significant effect on brand equity of PT. Bank Mandiri Branch Jakarta Gedung Jaya. On the other hand, sales promotio dan, direct marketing have negative effect on brand equity of PT. Bank Mandiri (Persero) Tbk.. Keywords: Integrated Marketing Communication, Branding Equity, PT. Bank Mandiri KCP Jakarta Pusat. PT. Bank Mandiri Branch Jakarta Gedung Jaya.